Optimising the early-stage rehabilitation process post-ACL reconstruction - Buckthorpe, M.; Gokeler, A.; Herrington, L.; Hughes, M.; Grassi, A.; Wadey, R.; Patterson, S.; Compagnin. A.; La Rosa, G.; Della Villa, F. (Sports Medicine, 2024)
Outcomes following anterior cruciate ligament reconstruction (ACLR) need improving, with poor return-to-sport rates and a high risk of secondary re-injury. There is a need to improve rehabilitation strategies post-ACLR, if we can support enhanced patient outcomes. This paper discusses how to optimise the early-stage rehabilitation process post-ACLR. Early-stage rehabilitation is the vital foundation on which successful rehabilitation post-ACLR can occur. Without high-quality early-stage (and pre-operative) rehabilitation, patients often do not overcome major aspects of dysfunction, which limits knee function and the ability to transition through subsequent stages of rehabilitation optimally. We highlight six main dimensions during the early stage: (1) pain and swelling; (2) knee joint range of motion; (3) arthrogenic muscle inhibition and muscle strength; (4) movement quality/neuromuscular control during activities of daily living (5) psycho-social-cultural and environmental factors and (6) physical fitness preservation. The six do not share equal importance and the extent of time commitment devoted to each will depend on the individual patient. The paper provides recommendations on how to implement these into practice, discussing training planning and programming, and suggests specific screening to monitor work and when the athlete can progress to the next stage (e.g. mid-stage rehabilitation entry criteria).